The importance of direct genetic testing for determining female carriers of the mutation in dystrophinopathies - Maksić, Jasmina; Maksimović, Nela; Rasulić, Lukas; Milankov, Olgica; Marjanović, Ana; Cvetković, Dragana; Rakočević Stojanović, Vidosava; Novaković, Ivana (Vojnosanitetski pregled, 2023)
Background/Aim. Duchenne muscular dystrophy (MD) and Becker MD are caused by mutations in the gene for dystrophin (DMD). They are X chromosome-linked reces-sive diseases where males are affected, and females are healthy carriers of the mutation in most cases. It is estimat-ed that 2/3 of mothers of Duchenne MD probands are car-riers, while 1/3 of probands have de novo mutations. The aim of the study was to confirm the carrier status of female members of the families of Duchenne MD/Becker MD probands using direct genetic testing methods. Methods. The study included 38 females from 31 families of Du-chenne MD/Becker MD probands with dele-tion/duplication in the DMD gene. Moreover, 4 cases of prenatal diagnosis of Duchenne MD/Becker MD were in-cluded. The methods of polymerase chain reaction - PCR and the multiplex ligation-dependent probe amplification - MLPA were applied for detecting deletions, i.e., dele-tion/duplication mutations in the DMD gene. Results. In the total of 31 Duchenne MD/Becker MD probands, 87.1% of deletions and 12.9% of duplications of one or more exons in the DMD gene were detected. Of the 29 tested mothers, mutations were found in 17 of them (14 de-letions and 3 duplications). Mutations were detected in 11 (57.9%) out of 19 mothers of probands with the Duchenne MD phenotype and 6 (60%) out of 10 mothers of Becker MD probands. Furthermore, 14 (56%) out of 25 mothers were carriers in probands with deletions, and 3 (75%) out of 4 mothers were carriers in probands with duplications. In the remaining 9 other female relatives of the patients, muta-tions were found in 4. In prenatal diagnosis, we identified a deletion in one male and one female fetus of one single mother who was confirmed as a carrier. Conclusion. The study showed that mothers were carriers in almost 60% of sporadic cases of Duchenne MD/Becker MD with dele-tions and duplications. In addition, the carrier frequency tended to be higher in mothers of the probands with dupli-cations (75%) compared to mothers of probands with dele-tions (56%).
Keywords: genes; genetic testing; muscular dystrophies; mutation; prenatal diagnosis; women